Effect of Different Cytokinins on Shoot Outgrowth and Bioactive Compounds Profile of Lemograss Essential Oil - Camas Reyes, Alberto; Vuelvas Nolasco, Rosalía; Cabrera Ponce, José Luis; Pereyra Alférez, Benito; Molina Torres, Jorge; Martínez Antonio, Agustino (PAGEPress Publications, 2022)
Lemongrass (Cymbopogon citratus) essential oil (EO) is a major source of bioactive compounds (BC) with anticancer activity such as α-citral, limonene, geraniol, geranyl acetate, and β-caryophyllene. Comparative studies about cytokinin effects on BC profiles in lemongrass are missing. Here, we evaluated four cytokinins (2iP, tZ, BAP, and KIN) in two different osmotic media, MS-N (3% sucrose, 3 g L−1 Gelrite™) and MS-S (5% sucrose, 5 g L−1 Gelrite™). It results in a higher multiplication rate in BAP containing medium compared to tZ, KIN, and 2iP (p ≤ 0.05). While shoots grown on MS-N/BAP, tZ, and KIN exhibited a highly branching morphology, MS-N/2iP produced a less branching architecture. BC profile analysis of established plants in pots revealed that their maxima production depends on the in vitro shoot growth conditions: i.e., highest content (80%) of α-citral in plants that were cultured in MS-S/BAP (p ≤ 0.05), limonene (41%) in MS-N/2iP, or geranyl acetate (25.79%) in MS-S/2iP. These results indicate that it is possible to increase or address the production of BC in lemongrass by manipulating the cytokinin type and osmotic pressure in culture media. The culture protocol described here is currently successfully applied for somatic embryogenesis induction and genetic transformation in lemongrass.